Causal role of immune cells in bipolar disorder: a Mendelian randomization study - Wang, Mengxuan; Wang, Shuo; Yuan, Guoshan; Gao, Mingzhou; Zhao, Xiyan; Chu, Zhenhan; Gao, Dongmei (Frontiers in Psychiatry, 2024)
Background The understanding of the immunological mechanisms underlying bipolar disorder (BD) has enhanced in recent years due to the extensive use of high-density genetic markers for genotyping and advancements in genome-wide association studies (GWAS). However, studies on the relationship between immune cells and the risk of BD remain limited, necessitating further investigation. Methods Bidirectional two-sample Mendelian Randomization (MR) analysis was employed to investigate the causal association between immune cell morphologies and bipolar disorder. Immune cell traits were collected from a research cohort in Sardinia, whereas the GWAS summary statistics for BD were obtained from the Psychiatric Genomics Consortium. Sensitivity analyses were conducted, and the combination of MR-Egger and MR-Presso was used to assess horizontal pleiotropy. Cochran’s Q test was employed to evaluate heterogeneity, and the results were adjusted for false discovery rate (FDR). Results The study identified six immune cell phenotypes significantly associated with BD incidence (P< 0.01). These phenotypes include IgD- CD27- %lymphocyte, CD33br HLA DR+ CD14- AC, CD8 on CD28+ CD45RA+ CD8br, CD33br HLA DR+ AC, CD14 on CD14+ CD16+ monocyte, and HVEM on CD45RA- CD4+. After adjusting the FDR to 0.2, two immune cell phenotypes remained statistically significant: IgD-CD27-% lymphocyte (OR=1.099, 95% CI: 1.051-1.149, P = 3.51E-05, FDR=0.026) and CD33br HLA DR+ CD14-AC (OR=0.981, 95% CI: 0.971-0.991, P = 2.17E-04, FDR=0.079). In the reverse MR analysis, BD significantly impacted the phenotypes of four monocytes (P< 0.01), including CD64 on CD14+ CD16+ monocyte, CD64 on monocyte, CX3CR1 on CD14- CD16-, CD64 on CD14+ CD16- monocyte. However, after applying the FDR correction (FDR < 0.2), no statistically significant results were observed. Conclusions This MR investigation reveals associations between immune cell phenotypes, bipolar disorder, and genetics, providing novel perspectives on prospective therapeutic targets for bipolar disorder.